Design of Information Systems for Food Distribution Control in LDPM Batutaba Sepakat - Novia Lestari (Universitas Bina Darma, 2019)
This study aims to assist LDPM (Community Food Distribution Institute) in facilitating the recording of transactions and distribution of grain from and to farmers so that it can provide information that can speed up the work process at LDPM Batutaba Agreed in serving farmers who sell grain at LDPM Batu Taba Sepakat. This information system itself was built using Object Oriented Programming Language, Delphi 7. With the SDLC system development model consisting of 7 (seven) steps, namely identification and selection, initiation and planning, analysis, logical design, physical design, implementation, and maintenance expected can create an information system that is in accordance with the needs of the LDPM Batu Taba Sepakat, so that there is an increase in food sales and distribution transaction data management that can improve the welfare of the people of Batu Taba, especially farmers.